A series of 2D and 3D coordination polymers containing multicore Mn-carboxyl chain and flexible polycarboxylate ligands: synthesis, structure, and magnetic properties. Issue 7 (30th April 2021) - Guo, Le; Gao, Yan-Peng; Lv, Yan-Hua; Wang, Li; Han, Yu; Chang, Fei
Abstract: We report the synthesis, crystal structures, and magnetic properties of a series of two-dimensional (2-D) and three-dimensional (3-D) coordination polymers (CPs). A solvothermal reaction of manganese metal salts with 4, 4′-oxydibenzoic acid (H2 oba), 4, 4′-methylenebis(oxy) dibenzoic acid (H2 mba), 4, 4′-(propane-1, 3-diylbis (oxy))dibenzoic acid (H2 pba) or 1, 4-bis (1H-imidazol-1-yl)-butane (bib) gives five new non-interpenetrating CPs, [Mn2 (oba)2 (CH3 OH)(H2 O)] (1 ), [Mn6 (oba)6 (bib)(DMF)2 (H2 O)4 ] · (DMF)2 (CH3 OH) (2 ), [Mn4 (mba)4 (bib)(CH3 OH)] (3 ), [Mn7 (pba)7 (bib)(H2 O)4 ] · (H2 O)3 (DMA)(CH3 OH)0.5 (4 ), and [Mn7 (pba)7 (H2 O)6 ](DMA)3 (5 ). The X-ray crystal structural analyses revealed that 1, 4, and 5 are 2-D layers, whereas 2 and 3 are 3-D frameworks with 1-D Mn-carboxylate chains. In 1, 2, 4, and 5, the 1-D Mn-carboxylate chains are formed by flexible carboxylate ligands and Mn ions; these were then linked by organic ligands in different directions, leading to the formation of 2-D and 3-D frameworks. Furthermore, IR, PXRD, elemental analysis, TGA, and magnetic properties have been investigated. Graphical Abstract: